Thalamic volume, resting-state activity, and their association with the efficacy of electroconvulsive therapy. (October 2019) - Takamiya, Akihiro; Kishimoto, Taishiro; Liang, Kuo-ching; Terasawa, Yuri; Nishikata, Shiro; Tarumi, Ryosuke; Sawada, Kyosuke; Kurokawa, Shunya; Hirano, Jinichi; Yamagata, Bun; Mimura, Masaru
Abstract: Electroconvulsive therapy (ECT) is the most effective antidepressant treatment. Biological predictors of clinical outcome to ECT are valuable. We aimed to examine multimodal magnetic resonance imaging (MRI) data that correlates to the efficacy of ECT. Structural and resting-state functional MRI data were acquired from 46 individuals (25 depressed individuals who received ECT, and 21 healthy controls). Whole-brain grey matter volume (GMV) and fractional amplitude of low frequency fluctuations (fALFF) were investigated to identify brain regions associated with post-ECT Hamilton Depression Rating Scale (HAM-D) total scores. GMV and fALFF values were compared with those in healthy controls using analysis of covariance (ANCOVA). Remission was defined by HAM-D ≤7. A multiple regression analysis revealed that pretreatment smaller GMV in the left thalamus was associated with worse response to ECT (i.e. higher post-ECT HAM-D). Pretreatment higher fALFF in the right anterior insula, and lower fALFF in the left thalamus and the cerebellum were associated with worse outcomes. The left thalamus was identified in both GMV and fALFF analyses. Nonremitters showed significantly smaller thalamic GMV compared to remitters and controls. We found that pretreatment thalamic volume and resting-state activity were associated with the efficacy of ECT. Our results highlight the importance of the thalamus as a possible biological predictor and its role in the underlying mechanisms of ECT action. Highlights: Structural and functional magnetic resonance imaging (MRI) assessments were conducted in 46 participants. A whole-brain multiple regression analysis revealed that pretreatment smaller left thalamic volume was associated with worse response to ECT. Pretreatment smaller fractional amplitude of low frequency fluctuations (fALFF) in the left thalamus were associated with worse response to ECT. Left thalamus was identified in both structural and functional MRI analyses. Our results highlight the thalamus as a critical region in the context of biological predictors and of the underlying mechanisms of ECT action.